Interacted toxic mechanisms of ochratoxin A and tricyclazole on the zebrafish (Danio rerio). (June 2023) - Wang, Yanhua; Deng, Meihua; Chen, Chen; Lv, Lu; Zhu, Hongmei; Chen, Liezhong; Weng, Hongbiao
Abstract: Despite the current efforts to identify the mixtures of chemical pollutants, they are often "binned" into their corresponding pollutant groups. Limited studies have investigated complex mixtures of chemical pollutants co-occurring across different groups. The combined toxic impacts of several substances become a critical consideration in toxicology because chemical combinations can exert a greater deleterious effect than the single components in the mixture. In the current work, we assessed the joint impacts of ochratoxin A and tricyclazole on the zebrafish ( Danio rerio ) embryos and explored their underlying signaling pathways. Ochratoxin A displayed higher toxicity than tricyclazole, with a 10-day LC50 of 0.16 mg L −1, whereas that for tricyclazole was 1.94 mg L −1 . The combination of ochratoxin A and tricyclazole exhibited a synergistic impact on D. rerio . The activities of detoxification enzymes GST and CYP450, as well as apoptosis-associated enzyme caspase 3, were distinctly changed in most individual and mixture exposures comparing to the untreated group. Upon both individual and mixture exposures, more dramatic variations were detected in the expressions of nine genes, such as the apoptosis genes cas3 and bax, antioxidant gene mn-sod, immunosuppression gene il-1β, and the endocrine system genes trα, dio1, trβ, ugtlab, and crh, compared with the untreated group. These findings suggested that the simultaneous exposure to low doses of mycotoxins and pesticides in food commodities was more toxic than predicted from the individual chemicals. Considering the frequent co-occurrence of mycotoxins and pesticides in the diet, this synergy should be considered in future assessments. Graphical abstract: Image 1 Highlights: Ochratoxin A had a higher toxicity to embryonic zebrafish than tricyclazole. Ochratoxin A in combination with tricyclazole showed synergistic toxicity. CarE had an important funcion in the synergism of ochratoxin A and tricyclazole. Expression levels of 9 genes in mixtures showed greater changes than individuals.